2001
DOI: 10.4049/jimmunol.167.6.3057
|View full text |Cite
|
Sign up to set email alerts
|

Gene Microarrays Reveal Extensive Differential Gene Expression in Both CD4+ and CD8+ Type 1 and Type 2 T Cells

Abstract: An important subdivision of effector T cells can be made based on patterns of cytokine production and functional programs. Type 1 T cells produce IFN-γ and protect against viral pathogens, whereas type 2 cells produce cytokines such as IL-4 and IL-5 and protect against large extracellular parasites. Both CD4+ and CD8+ T cells can be polarized into type 1 or type 2 cytokine-secreting cells, suggesting that both populations play a regulatory role in immune responses. In this study, we used high-density oligonucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
1

Year Published

2005
2005
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 50 publications
6
84
1
Order By: Relevance
“…After 48 h, the effects of IL-12 were clear and altogether 41 genes became regulated by IL-12 (Table II). Among these were only a few genes, such as SOCS3, CEBPB, and IL-7R that have a previously described role in Th1 and Th2 cell responses (13,19,20). Most of the genes regulated by IL-12 were also regulated by IL-4 and/or activation alone (Fig.…”
Section: The Slow Response To Il-12mentioning
confidence: 84%
See 2 more Smart Citations
“…After 48 h, the effects of IL-12 were clear and altogether 41 genes became regulated by IL-12 (Table II). Among these were only a few genes, such as SOCS3, CEBPB, and IL-7R that have a previously described role in Th1 and Th2 cell responses (13,19,20). Most of the genes regulated by IL-12 were also regulated by IL-4 and/or activation alone (Fig.…”
Section: The Slow Response To Il-12mentioning
confidence: 84%
“…We have conducted a genome-wide screening to identify novel genes involved in early Th1 and Th2 differentiation (13,15). Interestingly, numerous factors with known or unknown function were identified to be implicated in the process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This latter issue also bears on the failure of gene array studies comparing Th1 and Th2 cells to note a difference in CD4 mRNA levels in these two cell types that would account for the data reported here. The surface difference we see is only twofold, which many array analyses use as a cut-off [23,24]. Some have suggested that IL-4 is a "dangerous" cytokine and that the pseudo-monoallelic nature of IL-4 gene expression is a mechanism evolved to limit production of this potentially harmful molecule [25].…”
Section: Discussionmentioning
confidence: 99%
“…Microarray experiments have been carried out on various immune cell subsets by a number of different investigators in order to understand gene expression differences during differentiation and activation. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] These studies have provided invaluable insight into comprehensive gene expression profiles that define many different immune cell subsets and states of differentiation and activation. In particular, a recent study detailed elegantly the genes expressed specifically in many subsets of the T-cell lineage.…”
Section: Introductionmentioning
confidence: 99%